INFLUENCE THE GROWTH OF EARNING ASSETS AND THE GROWTH OF THIRD-PARTY FUNDS AGAINST THE OPERATIONAL BANK PERFORMANCE LISTED ON THE INDONESIA STOCK EXCHANGE - Suharto, Ade Buwono; Hariadi, Bambang (Jurnal Ilmiah Mahasiswa FEB, 2013)
The banking sector is one of the institutions that play an important role in the economy sector of some country, where the main operations in the banking sector are collecting funds from the public in the form of deposits and channeling back to the publicÂ  in the form of credit or another forms in order to improve the living standards of the peoples . As the company in general, efficient operational performance, are absolutely necessary to achieve the company's goal every year is no exception companies in banking, where revenue and expense management becomes the main thing that needs to be considered by the management company where this is in accordance with the company's main banking operations . This study aimed to investigate the relationship between growth in earning assets and deposits perumbuhan of operating performance is measured by the ratio of Operating Expenses to Operating Income (BOPO) by quantitative methods either simultaneously or partially. Which in this study, researchers found that the simultaneous testing growth of earning assets and the growth of third-party funds jointly affect the BOPO ratio. In a partial test researchers found earning asset growth has a significant impact and negatively related to BOPO ratio in which any increase of productive assets will push the value of the BOPO ratio,Â  and another case in the growth of third-party funds partially, researchers found that the growth of third-party funds not have a significant effect on the BOPO ratio. Key Word: Earning Assets, Third-party funds, Operasional Bank Performance